Composite poorly differentiated mucoepidermoid carcinoma of the thyroid and follicular variant of papillary thyroid carcinoma. Report of a case and review of the literature. Issue 4 (3rd April 2019) - Jayakody, Nimeshi S; Faoury, Morad; Fraser, Lisa R; Jogai, Sanjay; Patel, Nimesh N
Abstract: Mucoepidermoid variant of thyroid carcinoma is a rare and complex disease. Securing a diagnosis and formulating an evidence-based treatment plan is challenging. A case report of a patient with the dual pathology of a composite mucoepidermoid carcinoma of the thyroid and a follicular variant of papillary thyroid carcinoma with malignant metastasis is presented in this article. We discuss the challenges in diagnosis, prognostic factors and management of this rare presentation by reviewing current literature.